Traffic and log data captured during a cyber defense exercise - Tovarňák, Daniel; Špaček, Stanislav; Vykopal, Jan (Data in brief, 2020)
Cybersecurity research relies on relevant datasets providing researchers a snapshot of network traffic generated by current users and modern applications and services. The lack of datasets coming from a realistic network environment leads to inefficiency of newly designed methods that are not useful in practice. This data article provides network traffic flows and event logs (Linux and Windows) from a two-day cyber defense exercise involving attackers, defenders, and fictitious users operating in a virtual exercise network. The data are stored as structured JSON, including data schemes and data dictionaries, ready for direct processing. Network topology of the exercise network in NetJSON format is also provided.
Keywords: Network traffic; Cyber defense exercise; Event log; Network flow; Cybersecurity; Syslog; KYPO